Music-induced cortical plasticity: Protocol for a systematic review - Isaiah Osei Duah Junior; Danielle S. Rodriguez; Cassandra M. Germain (PLoS ONE, 2026)
Music engages sensory, motor, cognitive, and emotional systems, making it a powerful model for studying experience-dependent neuroplasticity. Although research on music-related brain changes is expanding, integration of structural, functional, and cerebrovascular findings remains limited, and effects on higher-order cognitive processes remain unclear. This systematic review will primarily synthesize evidence on music-induced cortical adaptations, including structural changes (e.g., gray and white matter alterations), functional modifications in neural networks, and cerebrovascular dynamics. Further, associations with behavioral measures such as attentional control, executive functioning, and language processing will also be examined when these outcomes are directly linked to the neural adaptations across the adult lifespan (≥ 50 years). The protocol was prepared in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) guidelines and has been indexed in International Prospective Register of Systematic Reviews (PROSPERO ID: CRD420251159362). The systematic review will be conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Using controlled vocabularies and medical subject headings (MeSH), a systematic search will be conducted across PubMed, Scopus, Web of Science, PsycINFO, EMBASE, CENTRAL (Cochrane Central Register of Controlled Trials), and Google Scholar databases, and supplemented by citation tracking from relevant review articles. Eligible studies will include randomized controlled trials (RCTs), non-randomized controlled trials, quasi-experimental, and observational designs (longitudinal, case-control, cross-sectional studies). The primary outcome will be changes in brain structure, function, and cerebrovascular hemodynamic activity following music intervention. Cognitive measures will be reviewed and consolidated as secondary endpoints. Data extraction, risk of bias and quality assessment will be performed independently by two reviewers using validated instruments, including Cochrane Risk of Bias 2 (RoB 2.0), Risk Of Bias In Non-randomized Studies – of Interventions (ROBINS-I), Risk Of Bias In Non-randomized Studies of Exposures (ROBINS-E), Strengthening the Reporting of Observational Studies in Epidemiology (STROBE), and National Heart, Lung, and Blood Institute (NHLBI) tools. A narrative synthesis will be conducted in accordance with Synthesis Without Meta-analysis (SWiM) guidelines, with meta-analyses undertaken where appropriate. Certainty of evidence will be assessed using Grading of Recommendations Assessment, Development, and Evaluation (GRADE) scale. Collectively, this protocol establishes a rigorous framework to systematically evaluate how music shapes the brain’s structure, function, and vascular systems, and how these changes translate into cognitive and behavioral outcomes.